2011
DOI: 10.1590/s0103-90162011000600009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the angular leaf spot reaction in common bean leaves and pods

Abstract: Information about genetic control of plant reaction to pathogens is essential in plant breeding programs focusing resistance. This study aimed to obtain information about genetic control of the angular leaf spot reaction in leaves and pods from common bean (Phaseolus vulgaris L.) line ESAL 686. This line was crossed with cultivars Jalo EEP 558 (resistant), Cornell 49-242 (resistant) and Carioca MG (susceptible). Generations F 1 , F 2 and backcrosses (BC 11 and BC 21 ) were obtained. In the dry season (2009), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 8 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…There was a predominance of additive effects in the genetic control of resistance to angular leaf spot, as demonstrated by the greater value for the sum of squares of the GCA (GCA 1 + GCA 2 ) than that for the sum of squares of the SCA. Borel et al (2011) also reported a predominance of additive effects in the genetic control of resistance to angular leaf spot when evaluating the natural occurrence of the disease in the field.…”
Section: Estimates Of Gca and Sca In Relation To Alsmentioning
confidence: 98%
See 1 more Smart Citation
“…There was a predominance of additive effects in the genetic control of resistance to angular leaf spot, as demonstrated by the greater value for the sum of squares of the GCA (GCA 1 + GCA 2 ) than that for the sum of squares of the SCA. Borel et al (2011) also reported a predominance of additive effects in the genetic control of resistance to angular leaf spot when evaluating the natural occurrence of the disease in the field.…”
Section: Estimates Of Gca and Sca In Relation To Alsmentioning
confidence: 98%
“…Amaro et al (2007) reported a gradation in symptoms among lines considered susceptible to angular leaf spot, and suggested that part of this gradation can be attributed to environmental effects and the polygenic control of the trait, because resistance to angular leaf spot has a complex inheritance. Borel et al (2011) also reported that the inheritance of resistance to angular leaf spot is complex in some situations, with low-effect genes and environmental effects acting together with large-effect genes or modifying genes.…”
Section: Estimates Of Gca and Sca In Relation To Alsmentioning
confidence: 99%
“…(Crous et al 2006). Disease symptoms occur in the aerial part of the plant, especially in the leaves and pods (Liebenberg and Pretorius 1997;Borel et al 2011). In trifoliate leaves, symptoms consist of small spots that range from dark gray to brown and are generally delimited by the leaf veins; these angular symptoms are characteristic of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating narrow sense heritability among crosses made with Kablanketi and Beti 10, Nanka, Nkanamna and Nanavala cutivars are moderate to high with regard to ALS resistance implying that these donor parents are suitable parents to be used for improvement of ALS resistance breeding programmes compared to the other parents. In a study conducted by Borel et al (2011) heritability in narrow sense estimates ranged from 0.19 to 0.68 in common bean. The heritability is not immutable; it depends on the population and environmental conditions in which individuals were grown.…”
Section: Heritability Studies For Als Resistancementioning
confidence: 99%
“…Therefore, selection and identification of resistant cultivar as well as the mechanism of resistance in resistant cultivars is paramount to deal with such a disease. The large variability of the pathogen necessitates the constant identification and characterization of resistance genes, understanding the genetics of the reaction to the pathogen (Borel et al, 2011) and subsequent development of resistant cultivars so as to minimize the risk associated with epidemics. Information about genetic control is very useful, because it helps breeders to choose the most efficient strategies for development of resistant and productive cultivars.…”
Section: Introductionmentioning
confidence: 99%